(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The neartic aphid Myzocallis (Lineomyzocallis) walshii (Mon.) is recorded for the first time in Italy. It infests the red Oak (Quercus rubra), on which leaves several generations per year develop.